100 of the world's best bars (Images, 2005)
100 of the World's best bars tours through Milan, London, Tokyo, Sydney, New York, and many more of te world most glamorous cities to capture the best and latest in disign for nightlife. From the humble pub to the dazzing discotheque, the featured bars cater to the desires of different customers, from small groups to office parties, and accommodate a broad range of entertaiment facilities.